FAKTOR-FAKTOR YANG MENDORONG WAJIB PAJAK PRIBADI UNTUK MENGGELAPKAN PAJAK - Hidayatulloh, Amir (Optimum: Jurnal Ekonomi dan Pembangunan, 2016)
The objective of this study is to determine the factors that encourage privatetaxpayers to tax fraud. These factors include attitude of non-compliance with tax,subjective norm, perceived behavioral control, and religiosity. Sampling this studyusing purposive sampling technique. The criteria used is taxpayer who has to haveNPWP, thus totaling 52 sample analyzed samples. This study uses survey data collection technique whether made directly or through the internet. Hypothesis testing is done by multiple regression analysis. This study obtained results the intention to tax fraud is effect by subjective norm, and perceived behavioral control, but an attitude of noncompliance with tax and religiosity does nor effect the intention tax fraud.